2015
DOI: 10.1590/s0080-623420150000300005
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care, Sense Of Coherence And Depression In Patients Hospitalized For Decompensated Heart Failure

Abstract: Objective:To analyze the self-care behaviors according to gender, the symptoms of depression and sense of coherence and compare the measurements of depression and sense of coherence according to gender. Method: A correlational, cross-sectional study that investigated 132 patients with decompensated heart failure (HF). Data were collected through interviews and consultation to medical records, and analyzed using the chi-square and the Student's t tests with significance level of 0.05. Participants were 75 men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
(38 reference statements)
2
14
0
9
Order By: Relevance
“…Homens e mulheres com IC podem ter experiências diferentes e, assim, usar estratégias distintas para confrontar a doença. Considera-se que as mulheres podem ter uma melhor percepção da saúde e construir estratégias mais eficientes de enfrentamento do que os homens (13) .…”
Section: As Variáveis Dicotômicas (Gênero E Escolaridade) Foram Analiunclassified
“…Homens e mulheres com IC podem ter experiências diferentes e, assim, usar estratégias distintas para confrontar a doença. Considera-se que as mulheres podem ter uma melhor percepção da saúde e construir estratégias mais eficientes de enfrentamento do que os homens (13) .…”
Section: As Variáveis Dicotômicas (Gênero E Escolaridade) Foram Analiunclassified
“…Only 36.6% participants regularly exercised every week. The study by Ferreira et al (2015), also showed a low percentage of participation in exercise among patients with HF (12.88%). Increasing physical activity is a suggested lifestyle intervention for patients, especially those with stable HF (Wexler et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Outras variáveis relacionadas à QVRS também têm sido avaliadas, como a presença de sintomas depressivos 12,13 e o senso de coerência (SC) 14,15 no contexto do pacientes com doenças cardíacas.…”
Section: Resultados De Estudos Realizados Com Indivíduos Comunclassified